2002
DOI: 10.1124/mol.62.3.608
|View full text |Cite
|
Sign up to set email alerts
|

Common Human UGT1A Polymorphisms and the Altered Metabolism of Irinotecan Active Metabolite 7-Ethyl-10-hydroxycamptothecin (SN-38)

Abstract: 7-Ethyl-10-hydroxycamptothecin (SN-38) is the pharmacologically active metabolite of irinotecan, in addition to being responsible for severe toxicity. Glucuronidation is the main metabolic pathway of SN-38 and has been shown to protect against irinotecan-induced gastrointestinal toxicity. The purpose of this study was to determine whether common polymorphic UDP-glucuronosyltransferase (UGT) affects SN-38 glucuronidation. First, kinetic characterization of SN-38-glucuronide (SN-38-G) formation was assessed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
244
2
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(256 citation statements)
references
References 33 publications
9
244
2
1
Order By: Relevance
“…Physiological function of UGT1A_i2 spliced forms J Bellemare et al described 6,7,11,12 and was reported as glucuronidation rates (area or pmol min -1 mg -1 protein).…”
Section: Glucuronide Formation Was Measured By Hplc-ms/ms Asmentioning
confidence: 99%
“…Physiological function of UGT1A_i2 spliced forms J Bellemare et al described 6,7,11,12 and was reported as glucuronidation rates (area or pmol min -1 mg -1 protein).…”
Section: Glucuronide Formation Was Measured By Hplc-ms/ms Asmentioning
confidence: 99%
“…64 This is consistent with the recent observation showing that the impact of the UGT1A1*6 allele on in vitro rates of SN-38 glucuronidation is modest compared to that observed for UGT1A1*27. 62 The hepatic UGT1A9 and the extrahepatic UGT1A7 enzymes were recently shown to be involved in the in vitro metabolism of SN-38. 62 Thus, polymorphisms in UGT1A7 and UGT1A9 along with the promoter polymorphism of UGT1A1 and functional SNPs present in its coding region, potentially represent significant risk factors for severe toxicity and could serve to predict the incidence of adverse events in patients undergoing irinotecan-based chemotherapy.…”
Section: Ugt1a1mentioning
confidence: 99%
“…Recent work has demonstrated that genetic variations affect glucuronidation rates and influence the risk of an individual to develop drug-induced toxicity. 35,37,[61][62][63][64] The role of genetic factors in determining variable rates of glucuronidation of hormones, tobacco smoke carcinogens, environmental pollutants and dietary components is poorly understood. Recent findings suggest that metabolic alterations may actually determine the degree of exposure of an individual to toxic or carcinogenic substances over a long time period and may contribute to modify one's susceptibility to diseases such as cancer.…”
Section: Introductionmentioning
confidence: 99%
“…(8) In addition to UGT1A1, other human UGT isoforms (e.g., UGT1A7 and UGT1A9) appear to catalyze SN-38G formation. (9,10) In addition to metabolism, another important route of irinotecan elimination is through biliary excretion. Among the several ABC transporters, ABCB1 and ABCC2 are the two main transporters involved in the biliary elimination of irinotecan and SN-38 species.…”
Section: Introductionmentioning
confidence: 99%